(untitled) (Progress Annals: Journal of Progressive Research, 2025)
This article presents the design of a press operating under high pressure to convert coal dust, generated during mining and transportation processes, into a usable form. The study addresses the challenges associated with the fine dispersion of coal particles, which significantly reduce their mechanical strength and combustibility. The proposed high-pressure press enables the compaction of raw coal dust into dense briquettes with improved structural integrity and energy characteristics. Particular attention is given to the design parameters of the press, the pressure distribution during compaction, and the optimization of binder content to ensure uniform briquette formation. Experimental analyses were conducted to evaluate the influence of pressing pressure and particle size distribution on the density, durability, and combustion properties of the briquettes. The results confirm that the application of high-pressure pressing not only reduces dust losses and environmental pollution but also enhances the efficiency of coal utilization in thermal energy production